A Reformation in Progress: The Path toward the Reform of Johannes Oecolampadius - Colombo, Matteo (Religions, 2024)
This article examines the life, theological career, exegetical development, and posthumous biographies of Johannes Oecolampadius as illustrative examples of the fact that the Swiss Reformation, with all its religious movements, was far from a uniform concept in terms of its origins, purposes, and methodologies. The article explains through Oecolampadius’s example an approach to reform that was ‘in progress’, traversing the nexuses of disparate methods and exegetical priorities. Oecolampadius’s experience occupied a position at the intersection between the authority of Patristics and the principle of sola scriptura, exemplifying a balance between the past and the present of Christian tradition. The path that led Oecolampadius to become a Protestant Reformer is characterised by a gradual transition, not abrupt, not radical. His example demonstrates the methodological and ideological diversity of the Reformation, which can be observed through the prism of a single life and its intellectual periods. His conversion offers insight into how these varied approaches shaped personal engagements with Scripture, and challenges the notion of an immediate or singular evangelical ‘calling’ or ‘conviction’. This article examines a specific phase within the broader and varied trajectory of the Swiss Reformation by analysing the transformation of Oecolampadius from a biblical scholar to a preacher, and eventually to a Reformer. This case study illustrates how disparate methodologies, whether rooted in humanism or Patristics, contributed to gradual and personal evolution, ultimately giving rise to distinctive individual stances on reform. This article presents a synthesis of three distinct perspectives on the question. The first part approaches the question through the lens of church history and intellectual history; the second one utilises the history of exegesis and New Testament scholarship; and the third draws upon the perspectives of Protestant historiography, from the standpoint of social history and the history of biographies in Early Modern times.